2018
DOI: 10.3389/fvets.2018.00084
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Historical Patterns in the Emergences of Novel Highly Pathogenic Avian Influenza (HPAI) H5 and H7 Viruses in Poultry

Abstract: Over the years, the emergence of novel H5 and H7 highly pathogenic avian influenza viruses (HPAI) has been taking place through two main mechanisms: first, the conversion of a low pathogenic into a highly pathogenic virus, and second, the reassortment between different genetic segments of low and highly pathogenic viruses already in circulation. We investigated and summarized the literature on emerging HPAI H5 and H7 viruses with the aim of building a spatio-temporal database of all these recorded conversions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 90 publications
0
95
0
4
Order By: Relevance
“…Reassortment was observed considerably in all non‐enzootic viruses detected in this study. This is highly evident in the case of H7N3 viruses as was seen in other regions . The genes of these viruses were related to genes from other Eurasian viruses of various subtypes.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Reassortment was observed considerably in all non‐enzootic viruses detected in this study. This is highly evident in the case of H7N3 viruses as was seen in other regions . The genes of these viruses were related to genes from other Eurasian viruses of various subtypes.…”
Section: Discussionmentioning
confidence: 55%
“…This is highly evident in the case of H7N3 viruses as was seen in other regions. 26 The genes of these Figure S2). Previous studies showed that the allele A AIVs are more common than allele B.…”
Section: Discussionmentioning
confidence: 99%
“…replicates (Stamatakis 2014). All HP clusters were flagged within the large-scale topologies according to the presence of more than one basic residue within the consensus cleavage site in the HA protein sequence, and by confirming their HP status with case reports in the literature (Dhingra, et al 2018).…”
Section: Large-scale Phylogenetic Analysismentioning
confidence: 99%
“…As a recent example, the outbreak of H7N9 viruses in early 2018 caused over 1567 infections and 615 deaths among people in China (Lam and Pybus 2018). Low virulence lineages of avian influenza viruses can mutate to highly virulent strains, resulting geographically and temporally independent HP outbreaks that have generated huge economic losses in the poultry industry, and pose an increased risk for avian-to-human spread (Dhingra, et al 2018) (Short, et al 2015). Thus, understanding the mechanisms driving the evolution of virulence in avian influenza viruses is critical.…”
Section: Introductionmentioning
confidence: 99%
“…The H7 subtype AIV has spread worldwide and has been detected in China (Wu et al, ), the United States (Olsen et al, ), Korea (Lee et al, ), Bangladesh (El‐Shesheny et al, ), Australia (Scott et al, ), Cambodia (Horwood et al, ) and Belgium (Van Borm et al, ). The pathogenic H7 subtype AIV changed from low pathogenicity in birds to high pathogenicity in both humans and birds (Dhingra et al, ). H7 subtype AIV can lead to severe economic losses in the poultry industry, and its rapid detection in the field can limit its spread in poultry and decrease the risk of human infection.…”
Section: Discussionmentioning
confidence: 99%